2019
DOI: 10.23893/1307-2080.aps.05701
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of uplc method for the determination of olopatadine hydrochloride in polymeric nanoparticles

Abstract: A new, simple, rapid, precise, accurate and specific stability indicating reverse phase UPLC method developed for the determination of encapsulated olopatadine hydrochloride (OLO) in the polymeric nanoparticle formulations. Studies were carried out on a 2.1x50 mm, 1.8 µm Zorbax Eclipse Plus C 18 column with an optimized mobile phase of methanol, water and sodium acetate buffer solution (40:50:10, v/v/v) at a flow rate of 0.5 mL/min. OLO was detected and quantitated using a photodiode array detector at a wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Since the RSD% values for both intermediate precision and repeatability were <2%, the method developed for theophylline was found to be precise according to the suggestions in ICH Q2(R1) guidelines [22].…”
Section: Results Of Precision and Repeatability Tests On Different Concentrations Are Given In Tablementioning
confidence: 95%
“…Since the RSD% values for both intermediate precision and repeatability were <2%, the method developed for theophylline was found to be precise according to the suggestions in ICH Q2(R1) guidelines [22].…”
Section: Results Of Precision and Repeatability Tests On Different Concentrations Are Given In Tablementioning
confidence: 95%
“… 117 Among liquid chromatographic techniques, UPLC has several advantages as it needs the sample in small volumes, shorter run times with decreased use of solvents and therefore is an economical method for rapid quantification of biomedical agents. 118 With this rationale, the data retrieved by UPLC was used in determining the quantitative load of rutin on rCNPs. In this regard, the retention time of standard rutin was 18.735 min; comparatively, the retention time for 0.22 micron filtered samples was 19.077 min ( Supplementary Figure 1A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that polymeric NPs fabricated using spray drying module to control particle size and distribution. The NPs obtained by spray-dryer showed good performance in terms of a high yield and encapsulation efficiency [16,17]. Polymer types, polymer concentration and amount of drug were optimized.…”
Section: Preparation Of Polymeric Nanoparticlesmentioning
confidence: 99%